Consider implementing 5 key strategies to help single parents succeed in higher ed. Issue 11 (25th January 2019) - Costa, Karen
Abstract : A 2017 report from the Institute for Women's Policy Research evaluated the status of single mothers in college. Key findings were that single mothers are a rapidly growing population, women of color are more likely to be single parents, and single mothers are particularly at risk for attrition.